UJI KAUSALITAS HUBUNGAN ANTARA HARGA BERAS DAN TINGKAT INFLASI DI SUMATERA SELATAN - Ully Rahmi Kay (Department of Development Economics, Universitas Sriwijaya, 2003)
The purpose of this study to determine the relationship between rice price and inflation rate in South Sumatera